Modern Marketing Strategies to Build Customer Expectations on Wedding Organizer Services Enter Management Kudus - Hakim, Moh Lukman; Handoyo, Ag.Sunarno; Sutono, Sutono (Global Insights in Management and Economic Research, 2025)
Purpose of the study: This study aims to analyze modern marketing strategies in building customer expectations for Enter Management Kudus wedding organizer services through the SWOT approach and the marketing mix framework (8P). Materials and methods: The research was conducted for one month at Enter Management Kudus, Purwosari, Central Java. Data were collected through observation, interviews, and documentation. Triangulation by source, technique, and time was applied to ensure data validity. Data analysis used the interactive Miles and Huberman model consisting of data reduction, data presentation, and conclusion drawing. Results: The findings show that Enter Management Kudus effectively implements key elements of modern marketing, including product diversification, flexible pricing, and digital promotion through social media. SWOT analysis positions the company in Quadrant I (aggressive strategy), highlighting strong internal capabilities and favorable external opportunities. Effective strategies include market expansion, service innovation aligned with current trends, and strengthening partnerships with local and national vendors. The company’s marketing approach integrates social media content, client testimonials, and creative collaborations, effectively shaping positive customer expectations and loyalty. Conclusions: Modern marketing strategies based on the 8P framework have strengthened Enter Management Kudus’s competitive position. The combination of service innovation, digital marketing, and customer relationship management successfully meets and exceeds client expectations. The results affirm that continuous innovation, consistent digital engagement, and quality enhancement are essential for sustaining customer satisfaction and brand growth in the wedding organizer industry.